Gambaran Pengetahuan Ibu tentang Malnutrisi pada Balita di Posyandu Dukuh Kendal Desa Sidodadi Kecamatan Sukosewu Kabupaten Bojonegoro tahun 2014 - Siti Patonah, Siti Patonah (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2014)
Â Â Â Â Â Â Â Â Â Â MalnutritionÂ is still a major problem in infants. Along with the times, malnutrition is still a major problem in infants. The high rate ofÂ Â malnutrition is influenced by several factors such as low levelsÂ ofÂ education Â (knowledge)Â aboutÂ the importance of maternal nutrition intakeÂ asÂ long asÂ theÂ child Â isÂ still Â Â in Â Â the Â processÂ of Â grow and develop. The condition of infants who came to Kendal Â IHC Â there are toddler body weight under Red lines on the KMS. Â Â Â Â Â Â Â Â Â Â The method used in this study was a descriptive survey approach.Variable in this study is theÂ mothersÂ knowledgeÂ aboutÂ malnutrition in children under five in Village Kendal Sidodadi, Sukosewu District, Bojonegoro regency. The Â population Â inÂ this study wereÂ allÂ mothersÂ with Â children Â Â underÂ five Â in village of Â Kendal Â Sidodadi, Â Sukosewu District ,Bojonegoro regency, amount 158 respondents and the sample was motherâs with toddlers who came to IHC Village Kendal, Sidodadi District,BojonegoroÂ regency totaled 109 respondents, the sampling used in purposive sampling. Data were collected by using a questionnaire later on though by way ofÂ editing, Â coding, Â scoring Â then Â tabulated Â and Â presented Â in Â the Â form Â of Â percentages wereÂ Â Â Â Â analyzed with descriptive analysis. Â Â Â Â Â Â Â Â Â The results showed that more than a majority of the respondents or mothers have good knowledge of malnutrition in children under five is 56 respondents (51.37%) of the 109 respondents. Â Â Â Â Â Â Â Mothers knowledgeÂ about malnutrition in under-five is good ,good Â motherâs knowledge would Â be Â useful if Â supported by the attitude and behavior of a true mother in feeding infants,Â Â Â Â Â so that children will not experience malnutrition. Keywords: Motrerâs,Knowledge , MalnutritionÂ Â